2016
DOI: 10.3847/0004-637x/819/2/95
|View full text |Cite
|
Sign up to set email alerts
|

Jet Signatures in the Spectra of Accreting Black Holes

Abstract: Jets are observed as radio emission in active galactic nuclei and during the low/hard state in X-ray binaries (XRBs), but their contribution at higher frequencies has been uncertain. We study the dynamics of jets in XRBs using the general-relativistic magnetohydrodynamic code HARM. We calculate the high-energy spectra and variability properties using a general-relativistic radiative transport code based on grmonty. We find the following signatures of jet emission: (i) a significant γ-ray peak above ∼10 22 Hz, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 80 publications
0
27
0
Order By: Relevance
“…This can be associated with change of states in black hole X-ray binaries. Further continuing the same set of GRMHD simulations, O'Riordan, Pe'er & McKinney (2016) showed that for a population of thermal electrons, during launching of the transient plasmoid, when BZ jet is quenched, the ratio of gamma-ray luminosity to X-ray luminosity becomes less than 1 while in the case of the steady BZ jet it remains greater than 1. Beskin & Zheltoukhov (2013), using a force free analytical solution under the assumption of axisymmetric and stationary flow, could explain the profile of the angular velocity of the field lines which were obtained from the 3D GRMHD simulations of McKinney, Tchekhovskoy, Blandford (2012).…”
Section: Introductionmentioning
confidence: 94%
“…This can be associated with change of states in black hole X-ray binaries. Further continuing the same set of GRMHD simulations, O'Riordan, Pe'er & McKinney (2016) showed that for a population of thermal electrons, during launching of the transient plasmoid, when BZ jet is quenched, the ratio of gamma-ray luminosity to X-ray luminosity becomes less than 1 while in the case of the steady BZ jet it remains greater than 1. Beskin & Zheltoukhov (2013), using a force free analytical solution under the assumption of axisymmetric and stationary flow, could explain the profile of the angular velocity of the field lines which were obtained from the 3D GRMHD simulations of McKinney, Tchekhovskoy, Blandford (2012).…”
Section: Introductionmentioning
confidence: 94%
“…We give the velocity in units of the Keplerian speed = v r 1 K . The "thinnermadx" models are those considered here (where the number x gives the spin), while the "thickdisk7" and "nonmad" models are the MAD and SANE models considered in O' Riordan et al (2016 Figure 11 we show the effects of varying f¢ v for a black hole with a=0.9. The difference between the observed and comoving power is a factor of  2 .…”
Section: A2 Dependence On the Fluid Velocitymentioning
confidence: 99%
“…100-122;Cadolle Bel et al 2006;Yuan et al 2007;Narayan & McClintock 2008;Niedźwiecki et al 2012Niedźwiecki et al , 2014Qiao & Liu 2015). However, it is also possible that a significant fraction of the X-ray emission originates in jets (e.g., Mirabel & Rodríguez 1994;Markoff et al 2001Markoff et al , 2003Markoff et al , 2005Markoff et al , 2015Falcke et al 2004;Bosch-Ramon et al 2006;Gupta et al 2006;Kaiser 2006;Kylafis et al 2008;Maitra et al 2009;Pe'er & Casella 2009;Pe'er & Markoff 2012;O' Riordan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the injected numerical density floors do not affect the dynamics, they can be artificially hot and so might affect the resulting spectra. In O' Riordan et al (2016aRiordan et al ( , 2016b, we considered the case where material from the central regions of the funnel does not contribute significantly to the observed spectrum. That is, we removed the floor material such that the middle of the funnel region was empty.…”
Section: Empty Funnel Prescriptionmentioning
confidence: 99%
“…This "empty funnel" situation can also be achieved by simply removing floor material from the funnel during the radiative transport calculation. The material to remove can be chosen in a number of ways, for example, as cells in a large bipolar cone (Shcherbakov & McKinney 2013), cells considered artificially hot or dense relative to their neighbors (Chan et al 2015b), or cells with a large value of σ (O' Riordan et al 2016aRiordan et al , 2016b.…”
Section: Introductionmentioning
confidence: 99%